Perceptions of English Deparment Students of Universitas Negeri Padang toward Kampung Inggris Pare in Improving Their Speaking Skills - Muhammad Najib Marzuq; Carbiriena Solusia (Journal of English Language Teaching, 2023)
This study investigated the perceptions of English Department students at Universitas Negeri Padang about Kampung Inggris Pare in improving their speaking skills and the benefits of studying there. A total of 22 students from the 2017-2023 batch participated in the study. Descriptive research with a quantitative approach was used to analyze the data. The research instrument was a questionnaire. The findings revealed that the students have a very positive perception of Kampung Inggris Pare's effectiveness in improving their speaking skills. This is reflected in the questionnaire's overall mean score of 3.61. The results of the study also showed that the English learning environment and methods in Kampung Inggris Pare helped students improve their speaking skills, develop their speaking skills in various aspects, and enhance their overall speaking skills. In other words, the study found that Kampung Inggris Pare is an effective place for English Department students at Universitas Negeri Padang to improve their speaking skills. This is due to the positive learning environment and effective teaching methods used there.